A missense mutation in human INSC causes peripheral neuropathy - Jui-Yu Yeh; Hua-Chuan Chao; Cheng-Li Hong; Yu-Chien Hung; Fei-Yang Tzou; Cheng-Tsung Hsiao; Jeng-Lin Li; Wen-Jie Chen; Cheng-Ta Chou; Yu-Shuen Tsai; Yi-Chu Liao; Yu-Chun Lin; et al. (EMBO Molecular Medicine, 2024)
Abstract PAR3/INSC/LGN form an evolutionarily conserved complex required for asymmetric cell division in the developing brain, but its post-developmental function and disease relevance in the peripheral nervous system (PNS) remains unknown. We mapped a new locus for axonal Charcot–Marie-Tooth disease (CMT2) and identified a missense mutation c.209 T > G (p.Met70Arg) in the INSC gene. Modeling the INSC M70R variant in Drosophila, we showed that it caused proprioceptive defects in adult flies, leading to gait defects resembling those in CMT2 patients. Cellularly, PAR3/INSC/LGN dysfunction caused tubulin aggregation and necrotic neurodegeneration, with microtubule-stabilizing agents rescuing both morphological and functional defects of the INSC M70R mutation in the PNS. Our findings underscore the critical role of the PAR3/INSC/LGN machinery in the adult PNS and highlight a potential therapeutic target for INSC-associated CMT2.